2023
DOI: 10.3390/ijms24021211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fetal Exposure to Endocrine Disrupting Chemical Mixtures on FOXA3 Gene and Protein Expression in Adult Rat Testes

Abstract: Perinatal exposure to endocrine disrupting chemicals (EDCs) has been shown to affect male reproductive functions. However, the effects on male reproduction of exposure to EDC mixtures at doses relevant to humans have not been fully characterized. In previous studies, we found that in utero exposure to mixtures of the plasticizer di(2-ethylhexyl) phthalate (DEHP) and the soy-based phytoestrogen genistein (Gen) induced abnormal testis development in rats. In the present study, we investigated the molecular basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Its overexpression suppresses the cAMP-induced expression of NUR77 and its target steroidogenic genes, resulting in decreased production of testosterone [ 73 ] and fertility defects [ 97 ]. Expression of Foxa3 in the testis is also modified upon exposure to DEHP [ 98 ]. The endoribonuclease RNAseL (male F1 DEG ×0.43) plays a role as a tumor suppressor, and polymorphisms in this gene are involved in prostate cancer [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its overexpression suppresses the cAMP-induced expression of NUR77 and its target steroidogenic genes, resulting in decreased production of testosterone [ 73 ] and fertility defects [ 97 ]. Expression of Foxa3 in the testis is also modified upon exposure to DEHP [ 98 ]. The endoribonuclease RNAseL (male F1 DEG ×0.43) plays a role as a tumor suppressor, and polymorphisms in this gene are involved in prostate cancer [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Soy consumption is commonplace among oriental populations and has recently become popular also in the western world, thus increasing the toxicological potential of PE-derived N-EDCs. PEs are also present in soy infant formula (SIF) that can be ingested by children [ 31 ]. Food contamination accounted for 32% of the sources of the N-EDCs identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to isoflavones causes changes in the morphology and physiological functions of the testicles. More specifically, in vivo studies have reported a decrease in testis size [ 31 , 34 ], changes in testis epithelium morphology [ 27 ] and a reduction in the weight of the epididymides, testes and seminal vesicles [ 35 , 36 ]. Mycotoxin administration also leads to a reduction in testicular weight of around 30% [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the same authors examined the effect of genistein on the germ cells of adult rats after prenatal exposure using doses typical of human diets. The results of this study indicated that, in utero, low doses of genistein together with DEHP exposure may disrupt the development of testicular cells, including Leydig cells [170]. Recently, in another study, acetaminophen (APAP) and genistein were used individually or in combination to evaluate their effect on two in vitro models of immature Sertoli cells: mouse Sertoli TM4 cells and postnatal day 8 (PND8) rat Sertoli cells.…”
Section: Genistein and Endocrine Disruptors In Testis Functionmentioning
confidence: 90%